Analisis Pemenuhan Kebutuhan Sarana Pendidikan Sekolah Dasar (SD) di Kecamatan Padang Utara Kota Padang Provinsi Sumatera Barat - Azmi, Nadya Al; Suasti, Yurni (ARZUSIN, 2024)
This research to analyze the availability of educational facilities and human resources (HR) in Elementary Schools (SD) in Padang Utara District, Padang City, West Sumatra Province. The research method used was descriptive with total sampling from 34 elementary schools in Padang Utara District. Primary data was obtained from the school concerned, while secondary data was obtained from supporting documents and literature. Data analysis was carried out through needs fulfillment analysis and descriptive analysis. The results of the research show that the availability of educational facilities in Padang Utara District elementary schools is included in the sufficient category, with the majority of elementary schools having adequate classrooms, laboratories, libraries and fields. However, IT facilities are still very minimal with only 4 elementary schools having them. Apart from that, the number of teachers in each elementary school in Padang Utara District is sufficient, and some schools even have excess teachers compared to standard requirements. This research concludes that although the availability of facilities and human resources at Padang Utara District Elementary School is quite adequate, there are still several areas that require improvement, especially in IT facilities to support a more effective learning process.